Differential Biophysical Behaviors of Closely Related Strains of Salmonella - Liu, Yameng; Hayes, Mark A. (Frontiers in Microbiology, 2020)
Salmonella is an important pathogen and is a world-wide threat to food safety and public health. Surveillance of serotypes and fundamental biological and biochemical studies are supported by a wide variety of established and emerging bioanalytical techniques. These include classic serotyping based on the Kauffmann–White nomenclature and the emerging whole genome sequencing strategy. Another emerging strategy is native whole cell biophysical characterization which has yet to be applied to Salmonella. However, this technique has been shown to provide high resolution differentiation of serotypes with several other paired strains of other microbes and pathogens. To demonstrate that biophysical characterization might be useful for Salmonella serotyping, the closely related strains sv. Cubana and sv. Poona were chosen for study. These two serovars were subjected to biophysical measurements on a dielectrophoresis-based microfluidic device that generated full differentiation of the unlabeled and native cells. They were differentiated by the ratio of electrophoretic (EP) to dielectrophoretic (DEP) mobilities. This differentiation factor is 2.7 ± 0.3 × 1010 V/m2 for sv. Cubana, versus 2.2 ± 0.3 × 1010 V/m2 for sv. Poona. This work shows for the first time the differentiation, concentration, and characterization of the Salmonella serotypes by exploiting their biophysical properties. It may lead to a less expensive and more decentralized new tool and method for microbiologists, complimenting and working in parallel with other characterization methods.